String Quartet in E-flat major, op. 127, theme from movt. 2, arrangement for voice and piano - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Schmidt, F. (poet):::Contributor:::::::::::: (B. Schott's Söhnen; Mainz; Germany)
The theme of the Adagio movement of the String Quartet in E-flat major, op. 127, transposed from A-flat to E-flat,, arranged for voice and piano, and supplied with words by F. Schmidt